Introduction to data acquisition with LabView - King, Robert H. (McGraw-Hill Companies, 2008)
Introduction; The LabVIEW environment; Data acquisition; Basic DAQ software design and flow control; DAQ state machines; Arrays; Input and output; High-Frequency DAQ.